2016
DOI: 10.15446/rfna.v69n1.54748
|View full text |Cite
|
Sign up to set email alerts
|

The probiotic Enterococcus faecium modifies the intestinal morphometric parameters in weaning piglets

Abstract: Global trends for animal production have seen a decrease in the use of antimicrobial compounds in feed, generating the need to implement new nutritional strategies that stimulate growth and promote intestinal health. This study aimed to determine whether the addition of E. faecium in drinking water improves intestinal morphometric parameters in post- weaning pigs compared with the probiotics strains L. acidophilus and L. casei on days 1 (21 days of age), 15 and 30 postweaning. The small intestine was completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…In the current study, the mean villus width was found to be increased in most cases as the age advanced (Table 1). It was decreased towards the caudal parts of the small intestine in both the groups, as also reported by Galeano et al (2016) in probiotic fed piglets. Dietary inclusion of probiotic and zinc revealed higher villus width in all segments of the small intestine in different age-groups (Fig 2).…”
Section: Villus Height and Width Crypt Depth And Width And Villus: Crypt Ratiosupporting
confidence: 83%
“…In the current study, the mean villus width was found to be increased in most cases as the age advanced (Table 1). It was decreased towards the caudal parts of the small intestine in both the groups, as also reported by Galeano et al (2016) in probiotic fed piglets. Dietary inclusion of probiotic and zinc revealed higher villus width in all segments of the small intestine in different age-groups (Fig 2).…”
Section: Villus Height and Width Crypt Depth And Width And Villus: Crypt Ratiosupporting
confidence: 83%
“…Consistently, indicated that dietary CB or EF improved the intestinal health development and absorption of nutrients in weaned piglets by reducing the crypt depth and incrementing the villus height. Also, in weaned piglets, EF enhanced the intestinal villi length (Galeano et al 2016). Additionally, Chen et al (2018) reported that the duodenal, jejunal, and ileal villus height was increased in lipopolysaccharide-challenged weaned piglets fed CB supplemented diet.…”
Section: Discussionmentioning
confidence: 90%
“…Probiotics have been proven to be beneficial for broiler breeding [14, 15]. E. faecium is a Lactobacillus genus that shows many positive effects on broiler growth and immunity [6, 7, 11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…E. faecium increases the concentration of organic acids and bacteriocins, which are important for the alimentary tract because of their nutritional benefits for enterocytes and their inhibitory effects on pathogens [8]. Previous studies have indicated that E. faecium improves the metabolism of macronutrients [7], promotes growth performance [6, 9], inhibits pathogen proliferation [1, 10], improves intestinal morphology [6, 11], and enhances the immune response [12]. Additionally, E. faecium prevents E. coli -induced intestinal disorders and manipulates the cecal microflora [1].…”
Section: Introductionmentioning
confidence: 99%